The Effect of Crude Oil Price on Merchandise Trade: Evidence from East Asia and Pacific - Bhenu Artha; Bahri; Cahya Purnama Asri; Ardhi Khairi; Fikri Alamsyah (Profesional Muda Cendekia Publishing, 2021)
One of the most important production inputs is energy, particularly crude oil. The impacts of oil price fluctuations on global trade flows can be understood by the uncertainty channel, fluctuations in oil prices may create uncertainty about the future path of the oil price, causing consumers to postpone irreversible purchases of consumer durable goods, and also causing firms to postpone irreversible investments, and also recent hikes and fluctuations in oil prices since 1999 have attracted attention and invoked concerns about their devastating effects on a variety of economic activities. The objective of this research is to determine the influence of crude oil price to merchandise trade in East Asia and Pacific. This research uses quantitative methods and linear regression analysis. The results of the analysis show that there is negative and significance effect of crude oil price on merchandise trade in East Asia and Pacific for the period 1987 – 2019.